2005
DOI: 10.1093/ndt/gfi177
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin attenuates renal injury in experimental acute renal failure ischaemic/reperfusion model

Abstract: Administration of EPO as a single dose before the onset of ischaemia produced a significant reduction in tubular injury, which was accompanied by a marked amelioration of renal functional impairment. The cytoprotective action of EPO against I/R injury seems to be associated with its anti-apoptotic action. Moreover, transcription factor NF-kappaB is likely to play a pivotal role in the pathophysiology of I/R renal injury and might have a key role in EPO-mediated protective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
1
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 17 publications
9
100
1
9
Order By: Relevance
“…Also apoptotic markers like BAX were reduced and the TUNEL assay showed only some positive cells. 9 This effect of renal tissue protection by EPO application was also seen in other rodent models. [10][11][12] Not only small animal models, but also experimental set-up with large animals that are much closer to clinical reality showed these positive effects.…”
supporting
confidence: 52%
“…Also apoptotic markers like BAX were reduced and the TUNEL assay showed only some positive cells. 9 This effect of renal tissue protection by EPO application was also seen in other rodent models. [10][11][12] Not only small animal models, but also experimental set-up with large animals that are much closer to clinical reality showed these positive effects.…”
supporting
confidence: 52%
“…A number of clinical and experimental studies have demonstrated that NF-κB, a transcription factor, plays a central role in renal pathology (6). Spandou et al reported that renal I/R leads to the activation of NF-κB, which suggests that it may be a marker of injury linked to the pathophysiology of a variety of renal disorders, including I/R, and that its inhibition prevents in vivo cell apoptosis associated with renal I/R injury (20). Therefore, inhibition of the permanent activation of NF-κB protects renal tissue from ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Akt can significantly increase NF-κB and HIF-1 activation resulting in the enhancement of EPO expression. Although in instances that involve some EPO receptorpositive tumors or specific ischemia-reperfusion cardiac injury models, EPO under most conditions uses NF-κB to prevent apoptosis through the enhanced expression and translocation of NF-κB to the nucleus to elicit anti-apoptotic gene activation [25,27,64].…”
Section: Wnt Gsk-3β Nf-κb and Epomentioning
confidence: 99%